Strengthening Transparency and Accountability as an Effort to Prevent Deviations in the Public and Private Sectors - Surjono, Welly (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
The research delves into the critical nexus between transparency, accountability, and misconduct within organizational governance structures. The purpose is to elucidate the multifaceted dynamics of these constructs and their implications for ethical conduct and integrity in both the public and private sectors. Adopting a qualitative research design, a comprehensive literature review is conducted to synthesize existing knowledge and perspectives on the topic. Various databases, including PubMed, JSTOR, Scopus, and Google Scholar, are utilized to identify seminal works and emerging trends. Findings underscore the pivotal role of transparency initiatives and accountability mechanisms in mitigating misconduct and promoting ethical governance. Insights from diverse disciplines, including political science, economics, and organizational behavior, contribute to a nuanced understanding of the subject. Implications of the research extend to policymakers and organizational leaders, highlighting the importance of developing evidence-based strategies to foster transparency, accountability, and ethical conduct. Integratingtechnology-enabled platforms for the public participation and monitoring, strengthening whistleblower protection, and enhancing anti-corruption enforcement are critical areas for intervention. The research underscores the imperative of interdisciplinary collaboration and sustained efforts to address systemic challenges and promote a culture of integrity and trust within organizational settings